CyTOF Measurement of Immunocompetence Across Major Immune Cell Types. Issue 1 (13th February 2018) - Subrahmanyam, Priyanka B.; Maecker, Holden T.
Abstract: The central role of the immune system is becoming appreciated in a wide variety of diseases. Cancer immunotherapy is one area that has yielded much recent success, although not all patients benefit equally. At the same time, recent studies have highlighted the heterogeneity of the human immune system. Despite this heterogeneity, we do not routinely measure immune competence in clinical practice, and there are no consensus assays of healthy immune function. Using mass cytometry (CyTOF), we can simultaneously detect ∼40 markers to identify various cell subsets and determine their function by the expression of cytokines, cytotoxicity, and activation markers. This can help assess 'immunocompetence' and facilitate better implementation of immunotherapies, both in specific disease settings and perhaps eventually as a prognostic tool in healthy subjects. Here we introduce the concepts behind this assay and provide a protocol that we have successfully implemented to identify possible predictive biomarkers of immunotherapy outcome. © 2017 by John Wiley & Sons, Inc.